Acute administration of the olive constituent, oleuropein, combined with post-conditioning mechanism exerts cardioprotective effects by modulating oxidative defense. (14th October 2021) - Tsoumani, M; Georgoulis, A; Nikolaou, P E; Kostopoulos, I; Dermintzoglou, T; Papatheodorou, I; Zoga, A; Efentakis, P; Papapetropoulos, A; Lazou, A; Skaltsounis, A L; Tsitsilonis, O; et al.
Abstract: Background/Introduction: Oleuropein (oleu), the main polyphenolic constituent of olive, has cardioprotective effects against ischemia (I) – reperfusion (R) injury (IRI) when administered chronically. Purpose: We aimed to assess the cardioprotection afforded by acute administration of oleu, to evaluate the underlying mechanism and whether it could enhance or imbed the cardioprotective manifestation of ischemic postconditioning (PostC). Methods: Male rabbits were subjected to I/R (30/180 min) and randomized to 7 groups: (i) Control (ii) PostC: 8 cycles of 30-sec I/R at the onset of R; (iii) Oleu (100 mg/kg, iv bolus) at the 20th min of I; (iv) Oleu+NOS inhibitor (L-NAME, 10mg/kg); (v) Oleu+PI3K/Akt inhibitor (wortmannin, 60 μg/kg); (vi) Oleu+JAK2 inhibitor (AG490, 6μg/kg/min) and (vii) Oleu+PostC. Additionally, male C57BL6/J mice, subjected to I/R (30/180 min) and randomized to 4 groups: (i) Control; (ii) PostC: 3 cycles of 10-sec I/R at the onset of R; (iii) Oleu (350 mg/kg, iv bolus) at the 20th min of I; (iv) Oleu+PostC. In both animal models, infarct size (IS) expressed as percentage of infarct to area at risk ratio (I/R, %) was determined. Oleu's effect on cardiomyocytes was measured by MTT assay in adult rat cardiomyocytes exposed to simulated I (SI) and reoxygenation. We also assessed the effect of oleu on mitochondrial permeability transition pore (mPTP) through calcium retention capacity (CRC) assay and on cGMP accumulation in rat aortic smooth muscle cells. In a mouse model of IRI, we explored the effect of oleu on the recruitment of inflammatory monocytes and neutrophils in the IR heart using flow cytometry, whereas the effect of oleu on Nrf-2 signaling pathway-related genes was analyzed by western blot. Results: In both animal models acute oleu administration reduced significantly the IS compared to the control group. None of the inhibitors of the classic cardioprotective pathways influence its IS limiting effects in rabbits. Combination of oleu with PostC caused further limitation of IS compared to PostC in both animal models (I/R Rabbits: 14.6±0.9 vs. 26.7±2.7%, p<0.01 and I/R mice: 11.5±1.8 vs. 20.3±1.8%, p<0.01). Oleu had a direct protective effect on cardiomyocytes since it significantly increased their viability following SI-reoxygenation injury as compared to non-treated cells. Oleu did not inhibit the calcium induced mPTP opening in isolated mitochondria and did not increase cGMP production. Oleu, PostC and their combination reduced inflammatory monocytes infiltration into the heart and the circulating monocytes. Oleu conferred additive cardioprotection on top of PostC, via increasing the expression of Nrf-2 and its downstream targets (HO-1 and SOD-2). Conclusion(s): Acute oleu administration combined with PostC provides robust and synergistic cardioprotection in experimental models of IRI by inducing antioxidant defense genes through Nrf-2 axis and independently of the classic cardioprotective signaling pathways. FUNDunding Acknowledgement: Type of funding sources: None.